Callus Proliferation from Immature Leaf Explants of Durian (Durio zibethinus Murr. cv. Selat) with the Addition of Picloram and BAP - Zulkarnain ,; , Lizawati (Jurnal Hortikultura Indonesia, 2013)
ABSTRACTThis study was aimed to obtain an appropriate medium composition with various combinations of Picloram + BAP for the proliferation of embryogenic callus from immature leaf explants of durian. The experiment was carried out at the Plant Biotechnology Laboratory,  Faculty of Agriculture ,  the University of Jambi from January through to November 2012. Five levels of Picloram (1.0, 2.0, 3.0, 4.0, 5.0 mg  L-1) in combination with three levels of BAP (0, 0.5, 1.5 mg  L-1) were tested. Therefore, there were 15 treatment combinations with 4 replicates resulting in  60 experimental unit. Each unit  consisted of 4 culture flasks containing one immature leaf explant. Cultures were kept in culture room with 16 h photoperiod and 1000 lux light intensity. The results showed that: 1) callus proliferation on immature leaf explants of durian cv. Selat was dependent upon the level of Picloram + BAP added to culture medium, 2) the addition of 3.0 -  5.0 mg L-1Picloram without BAP was found to be effective in promoting callus proliferation on the majority of cultured explants, 3) all regenerated callus showed similar characteristics, but embryogenic properties was not seen yet, and 4) the application of tissue culture technique in the propagation of durian cv. Selat needs further comprehensive  investigation, particularly on factors directly affecting culture development and inducing somatic embryogenesis.Key words: tissue culture, in vitro culture, micropropagation, plant hormones, auxin, cytokinin, fruit crops. ABSTRAKPenelitian  ini  bertujuan  untuk  mendapatkan komposisi  media  yang  tepat dari  kombinasi Picloram + BAP untuk proliferasi kalus embriogenik dari eksplan daun dewasa durian. Penelitian dilakukan  di  Laboratorium  Bioteknologi Tanaman,  Fakultas  Pertanian,  Universitas  Jambi  dari Januari hingga November 2012. Perlakuan kombinasi media zat pengatur tumbuh adalah lima taraf Picloram (1.0, 2.0, 3.0, 4.0, 5.0 mg L-1) dengan kombinasi tiga taraf perlakuan BAP (0, 0.5, 1.5 mg L-1).  Terdapat  15  kombinasi  media perlakuan dengan  4  ulangan,  sehingga  terdapat  60  kombinasi satuan percobaan. Setiap unit percobaan terdapat 4 botol kultur dengan satu eksplan daun. Kultur disimpan di ruang kultur selama 16 jam penyinaran dan intensitas cahaya 1000  lux. Hasil penelitian menunjukkan bahwa: 1) Proliferasi kalus dari eksplan daun  muda buah  durian tergantung pada taraf kombinasi  picloram  +  BAP yang  ditambahkan  ke  media  kultur;  2)  Penambahan  3.0-5.0  mg  L-1Picloram  tanpa  BAP  memberikan  hasil  yang  efektif  untuk  menginduksi proliferasi  kalus  pada sebagian besar eksplan; 3)  Regenerasi kalus menunjukkan karakteristik serupa, tetapi embriogenik kalus  tidak  muncul, dan 4)  Perbanyakan  eksplan  daun  durian  dengan  tehnik  kultur jaringan membutuhkan penelitian lebih  lanjut, terutama pada faktor yang berpengaruh langsung pada induksi embriogenesis somatik.Kata kunci: auksin, buah, kultur jaringan, kultur in vitro, mikropropagasi, sitokinin, zat pengaturtumbuh,